Students' Misconceptions in High School Biology Subjects - Melina rahmi; Zulyusri Zulyusri (Biology Education Department, Faculty of Teacher Training and Education, University of Nahdlatul Wathan Mataram - Indonesia, 2021)
Misconceptions understand concepts that are different from scientific concepts that have been approved by experts in their fields and can cause difficulties for students in understanding material. On average, there are still many students who still experience misconceptions in Biology material with different percentages for each material. The purpose of this study was to examine the results of the analysis of students' misconceptions on Biology material from 7 articles selected from 32 relevant sources. The type of research used is a meta-analysis with literature review research methods through literature studies using several data sources such as articles in electronic journals and books. The results showed that students experienced misconceptions in high school biology material studied by researchers in source articles with different percentages. Continuous misconceptions can harm students and prevent students from understanding the material well, which will result in students failing to understand new concepts, and it will continue with other related material.